Design and Application Research of a Digital Human Resource Management Platform based on ChatGPT - Zhou, Jinbo; Cen, Weiren (Journal of Theory and Practice of Social Science, 2023)
This research aims to explore whether a digital human resource management platform based on ChatGPT offers more advantages in providing personalized employee experiences, enhancing decision-making efficiency, and improving work productivity compared to traditional human resource management platforms. In terms of methodology, the working principles and model structure of ChatGPT are elaborated, followed by the introduction of the design and development approach for the digital human resource management platform based on ChatGPT. Furthermore, the innovative aspects of this platform are emphasized, particularly its dialogue generation capability and personalized user experience. The study findings indicate that the digital human resource management platform based on ChatGPT demonstrates significant advantages in personalized employee experiences, decision-making efficiency, and work productivity, holding greater potential and value compared to conventional human resource management platforms. Nevertheless, successful application of the platform necessitates further exploration and refinement to address data privacy and security concerns, provide appropriate training and support, and continuously improve and innovate platform functionalities and performance. The research contributes to the evolution and innovation of human resource management theory, offering more intelligent and personalized human resource management solutions, and delivering high-quality human resource services for organizations.